Students' Perception of the Importance of the Use of Information Technology in Higher Education at Dongola University and the Difficulties they Face - Majzoob Ahmed Mohammed Gamer (University of Science and Technology, Yemen, 2017)
Abstract:  This study aimed to identify the effectiveness of using information technology media and communication in university education from the students' perspective and the difficulties they face at Dongola University, and the effect of some variables (specialization, gender, and level of education, experience) on that, using the descriptive method.  To achieve this goal, the researcher developed a questionnaire as a tool for the study which included  (27) and were divided into three major themes. The sample of the study consisted of (240) male and female students in the academic year, who were chosen by the stratified random method. The results of the study showed that the degree of the students' perceptions of the effectiveness of using information technology media and communications  at university and the difficulties they face was moderate where the total average of the items was (70.17%) which is at a very moderate level. Also, no statistically significant differences were found that could be due to gender, specialization and experience student. However,  statistically significant differences at (a=0.05) in the difficulties they face were found which could be attributed to level of education in favor of the first level students. Finally, in light of these results and discussion, the study ended with a set of  conclusions and recommendations.